Analysis of Project-Based Differentiated Learning Management on Elementary School Student Activeness - Hasannudin, Hasannudin; Utaminingsih, Sri; Hariyadi, Ahmad (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aims to analyze the relationship between project-based differentiated learning management and elementary school students’ activeness, focusing on how differentiated learning (X1) and project-based learning (X2) are associated with student activeness (Y). Method: The study used a mixed methods approach with a sequential explanatory design. The quantitative phase involved a Likert-scale questionnaire administered through total sampling to 8 teachers at SDN Kadilangu. Instrument reliability was tested using Cronbach’s Alpha, followed by descriptive analysis and a Shapiro–Wilk normality test to determine the appropriate correlation technique. Because one variable was not normally distributed, Spearman correlation was applied. The qualitative phase employed a case study approach using classroom observations, in-depth interviews with teachers, the principal, and students, and document analysis to explain the quantitative patterns. Results: The instruments were reliable (α = 0.828 for X1; α = 0.788 for X2). Descriptive results showed high implementation of differentiated learning (M = 3.86) and project-based learning (M = 3.93), with high student activeness (M = 4.00). Spearman analysis revealed positive and significant relationships between differentiated learning and student activeness (r = 0.749; p < 0.05) and between project-based learning and student activeness (r = 0.786; p < 0.05). Novelty: The novelty of this study lies in examining the management dimensions of differentiated learning and project-based learning simultaneously. Previous studies have largely focused on outcomes, but have paid less attention to how teachers manage planning, organization, implementation, and evaluation in classroom practice. This study addresses that gap by analyzing how these management processes shape student activeness